2016
DOI: 10.1097/md.0000000000004929
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital medical complications associated with stroke recurrence after initial ischemic stroke

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
4
17
0
1
Order By: Relevance
“…Previous studies demonstrated that pneumonia and urinary tract infection were the most common clinical complications after an ischemic stroke, increasing morbidity and mortality 21-23 . The frequency of these complications in the study population was very similar to previous published studies; pneumonia between 10.6% and 21.2% 6,24-25 , and urinary tract infection between 3.2% and 5.0% 6,24 . There is a reciprocal interaction between complications and hospital stay; the infection retards the discharge, and the length of stay increases the risk of infection 26 .…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies demonstrated that pneumonia and urinary tract infection were the most common clinical complications after an ischemic stroke, increasing morbidity and mortality 21-23 . The frequency of these complications in the study population was very similar to previous published studies; pneumonia between 10.6% and 21.2% 6,24-25 , and urinary tract infection between 3.2% and 5.0% 6,24 . There is a reciprocal interaction between complications and hospital stay; the infection retards the discharge, and the length of stay increases the risk of infection 26 .…”
Section: Discussionsupporting
confidence: 89%
“…These complications included pneumonia, urinary tract infection, HT, gastrointestinal bleeding (GIB), deep vein thrombosis, pulmonary embolism, seizures and brain herniation. The definition of each complication was consistent with that in previous studies (Table 1) [4,18].…”
Section: Methodssupporting
confidence: 64%
“…Medical complications impede optimal recovery after ischemic stroke and are potentially life‐threatening. Accumulating evidence indicates that complications are common in stroke patients and strongly associated with mortality, disability and stroke recurrence after ischemic stroke . For example, hemorrhagic transformation (HT), the most feared complication after intravenous thrombolysis in acute ischemic stroke, limits the widespread use of reperfusion therapies such as anticoagulation and thrombolysis, resulting in the particularly poor outcomes associated with ischemic stroke, especially cardioembolic infarction .…”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study conducted at the Belgrade stroke institutions revealed that the most frequent infections among the AIS patients were urinary tract, intections (UTI) (17.7%) and chest infections (9.7%) 22 . It is well known that complications are associated with worse outcome in those patients 23 . Further, in Korea, the nurses are included in the Stroke Alerts Teams (SAT) organized with the aim to accelerate time to thrombolysis in the patients with AIS 24 .…”
Section: Discussionmentioning
confidence: 99%